Python for chemists - Hill, Christian, 1974-; Hill, Christian (Cambridge University Press, 2024)
"This accessible and self-contained guide provides a comprehensive introduction to the popular programming language, Python, with a focus on applications in chemistry and chemical physics. End of chapter problems are included throughout, with worked solutions available, and additional resources are provided on a companion website"--